2022
DOI: 10.3390/ani13010110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dietary Inclusion of Allium mongolicum Regel Extract on Serum Index and Meat Quality in Small-Tailed Han Sheep

Abstract: The aim of this study was to evaluate the effects of Allium Mongolicum Regel ethanol extract (AME) on the serum index and meat quality of lambs. A total of 30 male Small-tailed Han sheep (3 months old) with an average weight of 33.60 ± 1.23 kg were divided randomly into one of two groups: the control group (CON) was offered a basal diet, and the AME group was offered a basal diet with supplementation 2.8 g·lamb−1·day−1 AME. The trial lasted for 75 days. AME supplementation significantly decreased the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Among them, CDC42BPB may affect the synthesis of 3-hydroxybutyric acid and thus the quality of meat ( Li et al, 2022 ). And “high-density lipoprotein particle, GO:0034364” ( LOC101120204 , LOC101120613 , and LOC105601867 ) ( Supplementary Table S11 ), which is a cellular component term involved in the transport of lipids ( Zhao et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, CDC42BPB may affect the synthesis of 3-hydroxybutyric acid and thus the quality of meat ( Li et al, 2022 ). And “high-density lipoprotein particle, GO:0034364” ( LOC101120204 , LOC101120613 , and LOC105601867 ) ( Supplementary Table S11 ), which is a cellular component term involved in the transport of lipids ( Zhao et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analyses of indices related to growth performance, serum parameters, ruminal fermentation, and fecal microbiota were analyzed using a general linear model routine in SPSS software (Version 25.0, SPSS Inc., Chicago, IL, USA). The effect of feeding system on all variables was analyzed with the statistical linear model: Y i = μ + D i + E, where Y i is the dependent variable, μ is mean value, D i means the fixed effect of feeding system, and E means the random effect [ 36 ]. Significance was determined at a level of p ≤ 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The extracts of AMR have been shown to regulate the rumen environment and FA metabolism by increasing the concentration of total VFA and propionic acid in the rumen and the contents of UFAs in the longissimus dorsi muscle of lambs (Liu et al, 2019). Recent research reported that C17:0, and C18:0, which correlated with the "mutton flavor" of Small-Tailed Han sheep were decreased by adding AME (Watkins and Frank, 2019;Zhao et al, 2022b). The structure of rumen microflora is closely related to FA deposition in the longissimus dorsi muscle.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of rumen microflora is closely related to FA deposition in the longissimus dorsi muscle. Diet supplemented with AME changed the rumen fermentation pattern and the structure of rumen microflora (Zhao et al, 2022c), thus influencing the FA metabolism by improving MUFA and PUFA deposition in longissimus dorsi muscle (Zhao et al, 2022b). Existing research has demonstrated that AMR has significantly modulating effects on rumen microbial flora and FA metabolism in mutton sheep, its potential modulating effects on the rumen of dairy cows remain unknown.…”
Section: Introductionmentioning
confidence: 99%